Dark: apuntes de la filosofía y la ciencia ficción sobre el viaje en el tiempo (Monográfico) - Paladines Paredes, Lenin Vladimir (2022)
Dark is a German series created by Baran bo Odar and Jantje Friese and produced by the Netflix digital platform. Released in 2017, throughout its three seasons, the series presents a plot that revolves around the concept of time travel, from a philosophical - fantastic perspective. In this work, it is analyzed how some philosophical conceptions of time influence Dark, especially that of circular time, or eternal return, raised by Friedrich Nietzsche in his works The Gay Science (1882) and Thus Spoke Zarathustra (1883). In another line, certain scientific postulates serve as the foundation for the development of the plot, such as Novikov’s Principle of self-consistency (1983), the paradoxes of time travel or the wormhole approach, according to the works by Einstein and Rosen (1935). In conclusion, the German production Dark offers a modern approximation of the possibility of time travel, compared to other audiovisual or cultural products that deal with the same topic, based on both philosophy and real and recent scientific theories, which contributes to the consolidation of an audiovisual product with a serious and solid premise, within the field of science fiction, through the execution of an argument that delves into concepts such as free will, predestination, the conception of time and the idea of time as influencing dimension in our behavior.